Smart Techwash / Nur Syafizah Mohd Aliman, Nini Syafini Zaidi … [et al.] - Mohd Aliman, Nur Syafizah; Zaidi, Nini Syafini; Husin, Marhain Hanani (2018)
This project is assigned to us to make the promotional plan for a new product development which are not yet launch in the market. Our product is a development from a basic commercial washing machine to a smart commercial washing machine with high technology enhancement. The development is inspired by the scenario of waiting time that having some problem because people tend to leave their laundry to finish.